Agreement between parents and clinicians on the communication function levels and relationship of classification systems of children with cerebral palsy. Issue 2 (April 2018) - Mutlu, Akmer; Kara, Özgün Kaya; Livanelioğlu, Ayşe; Karahan, Sevilay; Alkan, Halil; Yardımcı, Bilge Nur; Hidecker, Mary Jo Cooley
Abstract: Background: Functional classification systems have generally been used by clinicians and recently by parents to classify various functions of children with cerebral palsy (CP). Objective: This study evaluated the agreement between clinicians and parents when classifying the communication function of children with CP using the Communication Function Classification System (CFCS). In addition, the relationships between the Gross Motor Function Classification System – Expanded and Revised (GMFCS-E&R), the Manual Ability Classification System (MACS), and CFCS were investigated. Methods: This study was a cross-sectional study and included 102 children aged 4–18 years with CP and their parents. The parents and clinician classified the communication of children by using the Turkish language version of CFCS. Furthermore GMFCS-E&R and MACS were used for classification only by the clinician. Results: The weighted Kappa agreement between CFCS results of the parents and clinicians was 0.95 (95% CI 0.95–0.96, p < 0.001). GMFCS-E&R levels were highly correlated with CFCS levels (r = 0.78 (95%CI 0.68–0.84, p < 0.001)). MACS and CFCS results were also highly correlated (r = 0.73 (95%CI 0.63–0.81, p < 0.001). Conclusion: The child's communication was classified as indicating higher functioning by the parents compared with the clinicians. The excellent agreement between parents and clinicians with the Turkish language version of CFCS for children with CP indicated that parents and clinicians could use the same language while classifying the communication function of children.